2012
DOI: 10.5194/nhess-12-1855-2012
|View full text |Cite
|
Sign up to set email alerts
|

Web-based Tsunami Early Warning System: a case study of the 2010 Kepulaunan Mentawai Earthquake and Tsunami

Abstract: <p><strong>Abstract.</strong> This study analyzes the response of the Global Disasters Alerts and Coordination System (GDACS) in relation to a case study: the Kepulaunan Mentawai earthquake and related tsunami, which occurred on 25 October 2010. The GDACS, developed by the European Commission Joint Research Center, combines existing web-based disaster information management systems with the aim to alert the international community in case of major disasters. The tsunami simulation sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Moreover, the size of the tsunami source becomes larger for the shallower focal depth. As anticipated, the size of the seismic area and the average slip in the source are governed by the focal depth (Aki, 1966;Kanamori and Anderson, 1979;Hebert et al, 2001Hebert et al, , 2005Ulutaş et al, 2012;Baptista et al, 2013;Mathias et al, 2013;Ulutaş, 2013). In the case of the shallow-focus earthquake (60 km), the height (the difference between the maximum bottom uplift and its maximum bottom subsidence) is 3.1 m, while in the deep-focus earthquake (609 km) the difference is 0.1 m ( Table 1).…”
Section: The Tsunami Sourcementioning
confidence: 77%
“…Moreover, the size of the tsunami source becomes larger for the shallower focal depth. As anticipated, the size of the seismic area and the average slip in the source are governed by the focal depth (Aki, 1966;Kanamori and Anderson, 1979;Hebert et al, 2001Hebert et al, , 2005Ulutaş et al, 2012;Baptista et al, 2013;Mathias et al, 2013;Ulutaş, 2013). In the case of the shallow-focus earthquake (60 km), the height (the difference between the maximum bottom uplift and its maximum bottom subsidence) is 3.1 m, while in the deep-focus earthquake (609 km) the difference is 0.1 m ( Table 1).…”
Section: The Tsunami Sourcementioning
confidence: 77%
“…The moment magnitude is considered to be a rigorous, accurate measurement of magnitude for large earthquakes with a strength C6.5, but takes at least 2 h to determine the magnitude of such earthquakes (Delouis et al 2009;Lomax and Michelini 2009), which is a relatively long time for application in a tsunami early warning system. Ulutas et al (2012) and Ulutas (2013) found that the average slip parameter was calculated to be 4.76 m according to the seismic moment of the earthquake.…”
Section: Introductionmentioning
confidence: 99%